THE IMPACT OF THE DIGITAL REVOLUTION ON FUTURE FIGHTER PILOT TRAINING - Ilie Claudiu MICLAUS MORARESCU (Journal of Defense Resources Management)
The Digital Revolution shall profoundly transform the landscape of future fighter pilot training, integrating advanced technologies to enhance efficiency, realism, and adaptability. Key innovations include virtual and augmented reality, big data analytics, an understanding of cortex development from a young age, the application of the athlete model, and a marked shift from legacy approaches to tech training methodologies. Legacy training approaches primarily relied on traditional classroom instruction, manual flight simulations, and live flight exercises. While effective, these methods are resource-intensive, costly, and limited in their ability to replicate the complexities of modern aerial combat. Pilots trained under these conventional systems often face constraints in terms of exposure to diverse combat scenarios and adaptive learning opportunities. In contrast, tech training approach leverages virtual and augmented reality to create immersive, realistic simulation environments that can replicate a vast array of combat situations with high fidelity, fostering a more challenging and realistic training experience. This approach can offer personalized training programs by identifying individual strengths and weaknesses through continuous performance monitoring. Understanding cortex development, particularly in young individuals, plays a critical role in shaping effective training methodologies. The cortex, responsible for critical functions such as decision-making, and attention, undergoes significant development during childhood and adolescence. Early engagement in activities that stimulate cognitive functions can enhance the cortex’s growth and plasticity, preparing individuals for advanced training later in life. The athlete model further revolutionizes pilot training by treating pilots as elite athletes.